Mindfulness as Relational: Participants' Experience of Mindfulness-based Programs Are Critical to Fidelity Assessments - Lynette M Monteiro PhD (SAGE Publishing, 2020)
Mindfulness outcome research has been criticized for issues in research design, precision of outcome measures, and reporting overoptimistically their power to effect change. Although mindfulness programs are a complex interaction of teachers, teachings, and participants, it is of some concern that current assessments of program fidelity focus primarily on teacher skills and program content delivery. Although ensuring that teachers are trained to criteria and adhere to program elements, the participants' engagement, a critical parameter contributing to outcomes of mindfulness programs, has been neglected. Furthermore, the assessment measures are primarily actuarial even when assessing experiential or difficult-to-define aspects of teacher-participant interactions. The inclusion of the participants' experience of the program as a component of fidelity assessments creates several opportunities to deepen our understanding of how mindfulness impacts the lives of practitioners. By investigating the teacher-participant relationship, determining how participants process the core elements, and exploring the implementation of the practices in their lives, a more nuanced understanding of the capacity of mindfulness-based programs to effect positive change may be possible.